Building hollow clay bricks embedding phase change material: Thermal behavior analysis under hot climate. (1st May 2022) - Hamdaoui, Said; Bouchikhi, Abdelhadi; Azouggagh, Mohammed; Akour, Mohamed; Ait Msaad, Abdelouahad; Mahdaoui, Mustapha
Highlights: The thermal behavior of four bricks incorporating a PCM was studied. A parametric study has been conducted to improve the bricks thermal behavior. Integrating PCM in bricks allowed increasing the time lag and reducing fluctuations amplitude. Volumes of HCBs and clay were reduced up to 30% and 35% for similar thermal behavior. Abstract: Numerous studies are focused on the thermal behavior evaluation of Hollow Clay Bricks (HCBs) integrating a Phase Change Material (PCM). In the major of these studies, the alveolar space is filled with PCM (macro-encapsulation). However, the air trapped in the alveoli is one of the assets of hollow bricks. Therefore, the present work is focused on the study of the thermal effects of integrating PCM into solid parts of HCBs (micro-encapsulation). Four types of HCBs of different dimensions and alveoli numbers (three, six, eight and twelve alveoli noted HCB-3, HCB-6, HCB-8 and HCB-12 respectively) were investigated. The thermal characteristics of PCM-Bricks such as thermal response, thermal storage capacity and thermal insulation capacity of the various HCBs were numerically evaluated and compared. The 2D-numerical simulations were carried out using Fluent software, based on the finite volume analysis and the enthalpy porosity based method. The results show that HCB type has notable effects on the thermal performance e.g. the phase shift induced by HCB-3, HCB-6, HCB-8 and HCB-12 was respectively of about 1 h, 1 h 43 min, 2 h 27 min and 4 h. In addition, the use of a PCM allowed to improve bricks thermal behavior. The HCB-3 with PCM exhibited equivalent thermal behavior to the HCB-6. Likewise, the HCB-8 with PCM offered equivalent thermal response to that of the HCB-12. Consequently, significant savings in volume, matter and energy have been achieved by introducing PCM in bricks. The volume of HCB has been reduced by up to 30% and a savings on matter was estimated to 35%.